Fundamentals of Governmental Accounting (Book). - Cannon, Arthur M.; Lorig, Arthur N. (The Accounting Review, 1951)
Reviews the book "Fundamentals of Governmental Accounting," 2nd ed., by Lloyd Morey and Robert P.Hackett.